Sifat Fisika Mekanika Papan Semen dari Limbah Penggergajian Berdasarkan Komposisi Jenis Serbuk Kayu Meranti Merah (Shorea Leprosula Miq) dan Terentang (Campnosperma Spp) : Mechanical physical Properties of Cement Board made from Sawmill Waste Based on Saw Dust Composition of Red Meranti (Shorea leprosula Miq) And Terentang (Campnosperma Spp - Sitorus, Sitorus; Koroh, Desy Natalia; Joni, Herwin; Sukarna, Raden Mas; Silvianingsih, Yosefin Ari (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2023)
This research aims to determine 1) the effect of the composition of red meranti and terentang sawmill waste to physical and mechanical properties of wood dust cement board according to SNI 03-2105-2006 and 2) determine the physical and mechanical properties of red meranti and terentang sawmill waste particle cement board the best based on SNI standards. The research method used a single factor Completely Randomized Design with five levels, namely A1(100% red meranti), A2(100% terentang), A3(50% red meranti: 50% terentang), A4(75% red meranti: 25% terentang) and A5 (25% red meranti: 75% terentang) using sawdust: cement ratio of 1:2, each treatment was repeated three times so that the number of sawdust cement boards made were fifteen pieces of sawdust cement board. The test parameters are physical properties (density, moisture content and thickness swelling) and mechanical properties (MoE, MoR and screw holding). Next, test the data for normality using Kolmogrov-Smirnov (SPSS 24). The results of research on the treatment of the composition of sawdust from red meranti and terentang using a cement sawdust ratio of 1:2 not significant effect on the physical and mechanical properties of sawdust cement board, because the specific gravity of red meranti wood and terentang did not significant different. The physical properties of sawdust cement board meet SNI 03-2105-2006, the best treatment was A1 (100% red meranti wood) for water content (9.09%) and thickness swelling (1.53%) while for density the best is in A4 powder composition (75 %: 25%, red meranti: terentang). The overall average value of mechanical properties does not meet SNI 03-2105-2006.